Fragment-based discovery of potent ERK2 pyrrolopyrazine inhibitors. Issue 21 (1st November 2015) - Burdick, Daniel J.; Wang, Shumei; Heise, Christopher; Pan, Borlan; Drummond, Jake; Yin, JianPing; Goeser, Lauren; Magnuson, Steven; Blaney, Jeff; Moffat, John; Wang, Weiru; Chen, Huifen
Graphical abstract: Abstract: A fragment-based lead discovery approach was used to discover novel ERK2 inhibitors. The crystal structure of N -benzyl-9 H -purin-6-amine1 in complex with ERK2 elucidated its hinge-binding mode. In addition, the simultaneous binding of an imidazole molecule adjacent to1 suggested a direction for fragment expansion. Structure-based core hopping applied to1 led to 5 H -pyrrolo[3, 2- b ]pyrazine (3 ) that afforded direct vectors to probe the pockets of interest while retaining the essential hinge binding elements. Utilizing the new vectors for SAR exploration, the new core3 was quickly optimized to compound39 resulting in a greater than 6600-fold improvement in potency.